CHANGES IN QUALITY INDICATORS OF DIFFERENT CUCUMBER HYBRID SEEDS DURING FIVE YEARS OF AGING: Aging of cucumber seeds during storage - Poštić, Dobrivoj (Journal on Processing and Energy in Agriculture, 2023)
The aim of the research was to evaluate the effect of year and seed hybrids on the most significant indicators seed quality of cucumber. Testing the quality of seeds of three different hybrids of cucumber: Centauro F1, Edona F1 and Solatio F1, was carried out during five years (2018 - 2022). Analysis of germination energy, total germination, abnormal seedlings and dead seeds cucumber showed highly significant differences (r
Keywords: cucumber, hybrid, germination